2011
DOI: 10.1111/j.1835-2561.2011.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

International Firm Lobbying and ED 8 Operating Segments

Abstract: Exposure Draft 8 (ED 8) Operating Segments was introduced to replace the revised IAS 14 Segment Reporting and to align segment reporting requirements with their United States counterparts in SFAS 131. ED 8 proposed material changes in the identification, measurement and disclosure of corporate segment information. In response to the ED, there were 182 comment letters from various respondents including firms, professional associations, regulatory authorities and accounting firms. This paper investigates the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 52 publications
1
13
1
3
Order By: Relevance
“…Generally speaking, our results seem consistent with a prior study on the ED IFRS 8 (Katselas et al, 2011), that revealed that larger firms, firms with more than three segments, and relatively profitable firms operating in an environment of high competition, were more likely to lobby in favor of ED 8.…”
Section: International Journal Of Accounting and Financial Reportingsupporting
confidence: 91%
See 1 more Smart Citation
“…Generally speaking, our results seem consistent with a prior study on the ED IFRS 8 (Katselas et al, 2011), that revealed that larger firms, firms with more than three segments, and relatively profitable firms operating in an environment of high competition, were more likely to lobby in favor of ED 8.…”
Section: International Journal Of Accounting and Financial Reportingsupporting
confidence: 91%
“…Unlike the past, this allows managers complete freedom to identify reporting segments only on the basis of the company decision making process. In other words, the implementation of IFRS 8 has increased the managerial discretion both to define the operating segment and to define the extent and evaluation criteria of the segment information disclosure (Véron, 2007;Katselas and Kang, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Increases of required disclosures in a post-IFRS environment raise concerns related to proprietary costs. Katselas et al (2011) find that lobbying firms opposing the implementation of IFRS 8 Segment Reporting cited the threat of releasing sensitive information to the market (i.e. potential proprietary costs) as a disadvantage of the proposed standard.…”
Section: Areas For Improvement In Disclosurementioning
confidence: 97%
“…In this sense, this setting differs from that found in prior studies that have generally considered lobbying arising in response to a single type of regulatory change, such as a change to accounting standards (Georgiou, 2004;Katselas et al, 2011;Stenka and Taylor, 2010).…”
Section: Resultscontrasting
confidence: 43%
“…Prior studies have generally considered lobbying arising in response to a single type of regulatory change (for example a change to accounting standards) (Georgiou, 2004;Katselas, Birt & Kang, 2011;Stenka & Taylor, 2010), and directed towards accounting standard setters (Walker & Robinson, 1993) whereas this study examines lobbying in response to the PC Inquiry whose recommendations had the potential to and ultimately did impact corporate reporting regulations at multiple levels. The recommendations were encapsulated in changes to accounting standards, corporate governance guidelines and corporations law.…”
Section: Background 421 Lobbying Literaturementioning
confidence: 99%